Pigovian transport pricing in practice - Beat Hintermann; Beaumont Maarten Schoeman; Joseph Molloy; Thomas Götschli; Alberto Castro; Christopher Tchervenkov; Uros Tomic; Kay W. Axhausen (University of Basel, Center of Business and Economics (WWZ), 2021)
Pigovian transport pricing was implemented in a large-scale field experiment in urban areas of Switzerland. The pricing varied across time, space and mode of transport. One third of the participants were given a financial incentive to reduce their external costs of transport, whereas others were provided information only or served as a control group. The pricing treatment caused a significant reduction in the external costs of transport. This reduction is a consequence of mode substitution and a shift of departure times. The effect of providing information in the absence of pricing was statistically significant only for subgroups of the sample.
Keywords: H23; H31; I18; Q52; Q54; R41; R48; 330; Transport pricing; pigovian taxation; mobility; external costs; congestion; tracking